Hubungan Personal Hygiene Ibu dan Sanitasi Lingkungan dengan Kejadian Diare di Puskesmas Pisangan Tangerang Selatan - Nisa, Alda Kurnia; Iriani, Dewi Utami (Journal of Religion and Public Health, 2023)
AbstractsDiarrhea is a health problem that still occurs frequently in the world. Diarrhea is one of the endemic diseases that still occurs in Indonesia and has the potential to become an Extraordinary Event (KLB). Diarrhea can be prevented by implementing good personal hygiene and environmental sanitation. The aim of this research was to determine the relationship between maternal personal hygiene and environmental sanitation with the incidence of diarrhea in toddlers at the Pisangan Health Center, South Tangerang. This research is a quantitative study with a cross-sectional study design. The population of this study were all toddlers who lived around the Pisangan Health Center area, East Ciputat District, Tangsel City, totaling 3390 toddlers. The sample criteria in this study were mothers who had toddlers aged 12 – 59 months around the working area of the Pisangan Community Health Center. The sample was determined as 75 respondents taken using cluster random sampling. Data collection was carried out in May – June 2023 through direct interviews with respondents using questionnaires and observations at the respondents' homes. This research uses bivariate statistical analysis of the Chi-Square test. The results showed that there were 46 cases of diarrhea (61.3%), there was a relationship between maternal personal hygiene (P-value = 0.001), clean water condition (P-value = 0.000), toilet condition (P-value = 0.000), condition SPAL (P-value = 0.00), condition of waste disposal facilities (P-value = 0.000) with the incidence of diarrhea in toddlers. In cases of diarrhea in toddlers, many factors are the cause, such as the mother's lack of personal hygiene regarding the habit of washing hands and cleanliness of eating utensils, poor environmental sanitation conditions are also one of the factors that play a role. More attention needs to be paid.Keywords: Personal hygiene; Sanitation; Toddler diarrhea